Knowledge of Snake Bite Management among Health Service Providers at a Rural Community of Bangladesh - Ahsan, HM Nazmul; Rahman, Md Ridwanur; Amin, Robed; Chowdhury, Enamul Hoque (Journal of Current and Advance Medical Research, 2018)
Background: Snake bile is a very common incidence among the rural people. Objective: This study was aimed to assess the pattern of snakebite in rural community through community engagement. Methodology: It uses the methodological triangulation qualitative and quantitative approach as well as a case study design in analyzing data, whereby the exploratory-descriptive design is followed. The findings from survey study on snake bite have been elicited from face to face interview with 243 number of medical professionals/health service providers consisting of 113 number of MBBS doctors, 86 number of nurses and 46 number of other health practitioners. The study area consisted of 5 zilla sadar hospitals and 15 upazilla health complexes. We purposively select the 243 sample(Doctors, Nurses, Paramedics ,Others) from the selected districts and its consisting random upazillas from the govt. sector hospitals keeping in mind gender balance (Male -Female) as a primary total target population. So in total, 5division and itsconsisting random upazilas hospital including union health complex hospital personnel will be interviewed throughout mention areas of Bangladesh. Result: Most of the health professionals (93.8%) stated that the existence of facilities in their respective hospitals is not adequate to manage the treatment of snake bite victims. Of the total number of medical personnel - around 30.0% of the health professionals had the opportunity to manage snake bite in their respective span of service (50.4% of MBBS docs + 11.6% of nurses + 11.4% of other practitioners).The findings show that majority of 87.6% of doctors, 85.0% of nurses and 95.5% of other practitioners mentioned rainy season as the most prevalent time for occurrence of snake bite in rural areas of Bangladesh. As for whether all snake bites are poisonous- around 17.0% of doctors followed by 18.6% of nurses and 16.0% of other practitioners are found to have wrong notion about mentioning that all snake bites are poisonous but in reality this is not true. Conclusion: There is insufficient knowledge, skill and experience of how to treat snake bite victims. Journal of Current and Advance Medical Research 2017;4(1):17-22